People Make Places: Rediscovering Hong Kong's Cultural Heritage through Placemaking - Cheung, Alan; Mui, Sarah; Cheung, Stephanie (MAJ - Malaysia Architectural Journal, 2025)
Hong Kong's rich cultural tapestry is embedded in its history, architecture and communities, connected by a genius loci rooted in its people. This paper demonstrated how One Bite Design Studio leveraged tangible, intangible, and everyday heritage as placemaking tools to build urban and rural communities via three local case studies. “Trolley Central” not only foregrounded the importance of overlooked, humble trolleys found in Hong Kong, but connected visitors with memories of the past. The heartfelt stories from trolley operators and makers fostered a holistic appreciation of everyday intangible culture in the urban streetscapes, using the humble trolley as a vessel to collect and share stories for the present and future generations. “Project House @1QRW”, convened in a well-preserved 1920s historical tonglau shophouse, was envisioned as a community living room that merged the past and present. The beautiful architecture triggered the fond memories of longtime residents and attracted them to participate in activities planned to bring residents and visitors together, reaffirming one’s sense of place and creating new identities and shared memories. Traditionally, Hong Kong’s story has centred on urban development and overshadowed the vibrant economic and cultural life of rural villages. As the curatorial partner for the “Sai Kung Hoi Arts Festival,” we spotlighted these underrepresented narratives by bringing artists and community stakeholders together in co-created art installations and public experiences. Our collective efforts transformed local villagers’ roles into active partners, and demonstrated how their rural culture and heritage could lead to a plausible pathway for rural revitalisation. These projects from Hong Kong not only shed light on the important role of culture and heritage in placemaking, but reflect the significance of community engagement in the process to building identity, sense of place and belonging, all foundational for developing resilient communities in urban and rural realms.